Differential effects of a single dose of Lisdexamfetamine and Guanfacine on cognitive function in children with ADHD - El Masri, Sahid; Kowalczyk, Olivia S.; Chiu, Tsz Hei; Criaud, Marion; Lukito, Steve; Mazibuko, Ndabezinhle; Salazar de Pablo, Gonzalo; Perez Rodriguez, Violeta; Makos, Orsolya; Lam, Sheut-Ling; Westwood, Samuel; Eaton-Turner, Alexander; et al. (Frontiers in Psychiatry, 2025)
BackgroundAttention-Deficit/Hyperactivity Disorder (ADHD) is associated with cognitive difficulties which improve with traditional stimulant and non-stimulant medications. However, there is limited evidence on the cognitive effects of the newer licensed stimulant lisdexamfetamine and non-stimulant guanfacine in children with ADHD. Therefore, we compared differential single-dose effects of lisdexamfetamine and guanfacine on cognitive performance in youth with ADHD.MethodsIn a randomized, placebo-controlled, double-blind, cross-over design, 22 children with ADHD were tested in tasks of sustained attention, vigilance, motor and interference inhibition, and time discrimination after single doses of guanfacine extended release, lisdexamfetamine, and placebo, with weekly washouts. Across tasks, composite measures of mean reaction time (MRT), intra-subject reaction time variability (coefficient of variation; CV), thought to reflect inattention, and premature responses were analyzed. Age-, IQ-, and sex- matched typically developing youth were assessed once without medication to test for potential drug normalization effects on performance differences compared to participants with ADHD on placebo.ResultsLisdexamfetamine significantly improved MRT and CV, while guanfacine worsened CV, compared with placebo and the other drug, with large effects. Although not reaching significance, there were moderate to large effects for lisdexamfetamine improving time discrimination and omission errors and for guanfacine to worsen omission errors in a sustained attention task relative to placebo and the other drug.ConclusionThese differential effects of lisdexamfetamine improving MRT and CV, while guanfacine worsening CV are clinically relevant, because they are the most replicated cognitive impairments in youth with ADHD. Findings suggest that guanfacine, unlike lisdexamfetamine, may not improve attention in children and adolescents with ADHD.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT03333668?term=NCT03333668&rank=1#study-plan, identifier NCT03333668.